Caracterización de la financiación para desarrollo en Colombia (2010-2018): Caso empresa ACME SA; Characterization of financing for development in Colombia (2010-2018) - Ingrid Giraldo Cardona; Félix O. Socorro Márquez; Giovanni E. Reyes (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The investigation focused on a financing problem, through the analysis of historical data, in a period of 8 years given the feasibility of comparable data, of the company ACME SA. The main objective of this study was to provide an updated characterization of ACME SA's investments, based on the country's departments and regions, taking into account: (i) each department in Colombia; (ii) each region of the country (Amazonian, Andean, Caribbean, Orinoquia and Pacific); (iii) departments according to competitiveness quartiles; (iv) departments according to quartiles of contribution to gross domestic product (GDP); and, finally, (v) departments according to population quartiles. The methodology used mainly was the linear regression technique. Based on this, the data were grouped by economic and departmental sector to analyze coverage. Therefore, the result of the study provides a highly grounded tool for decision-making, such as directing the strategy for prioritizing development through highly relevant indicators such as GDP, population, and competitiveness.
Keywords: G11; G24; G28; H54; 330; characterization; financing; development; decision-making; prioritization